Uwagi o aksjologicznych aspektach działalności legislacyjnej w dziedzinie prawa publicznego (konstytucyjnego) w Polsce - Winczorek, Piotr (Wydział Prawa i Administracji UAM, 1994)
The paper concerns axiological problems arising in connection with the fundamental changes of the Polish constitutional law after the fall of the communist system. The author considers possibilities of legitimising the laws made in communist Poland and their binding force in Poland today. Further, axiological assumptions of the legal system being currently constructed and dilemmas connected with this task have also been discussed. In consideration of axiological pluralism of the contemporary Polish society, every attempt to provide normative solution in the field of constitutional law must be described either as compromising between various axiological approaches or enforcing one axiological option.
Some remarks on the axiological aspects of legislative work on the constitutional law in Poland